Microfinance and Women Entrepreneurship with special reference to Bhopal (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper examines the impact of microfinance on women entrepreneurs in Bhopal, Madhya Pradesh, with a focus on the successes, challenges, and opportunities within this domain. Microfinance has emerged as a pivotal tool for promoting economic empowerment among women, particularly in developing regions where financial exclusion remains a significant barrier. Through the lens of case studies, the paper highlights how access to micro-credit has enabled women in Bhopal to transform their entrepreneurial dreams into reality, thereby improving their economic status and contributing to the local economy. The paper also explores the persistent challenges faced by women entrepreneurs in Bhopal, including limited access to finance, insufficient business skills, and socio-cultural barriers. The effectiveness of government schemes like the Stand-Up India and Mudra Yojana initiatives is assessed, revealing both the potential and the limitations of these programs in supporting women-led microenterprises.